1987
DOI: 10.1111/j.1530-0277.1987.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procollagen Type III N‐Terminal Peptides and Laminin P1 Peptide in Alcoholic Liver Disease

Abstract: The appearance of perivenular fibrosis on liver biopsy reflects the beginning of the fibrotic process that ultimately results in liver cirrhosis. To examine whether the fibrogenic activity can be detected by blood tests, we evaluated whole antibody radioimmunoassay (RIA) of procollagen type III N-terminal peptides (P-III-P), RIA of these peptides using Fab fragments (Fab-P-III-P), and RIA of the laminin P1 peptide in alcoholics within 1 week of alcohol abstinence. The Fab-P-III-P levels in subjects with perive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
4
31
1
1
Order By: Relevance
“…Based on the results, he concluded that patients who developed severe liver fibrosis had significantly higher concentrations of PIIINP (1208 ± 154 cpm/mg) than patients who did not develop liver fibrosis (734 ± 138 cpm/mg) (Torres-Salinas et al 1986). His findings were confirmed by other scientists in various research centers (Bentsen et al 1978, Nouchi et al 1987, Trinchet et al 1992, Oberti et al 1997, Tran et al 2000, Stickel et al 2001). However, we failed to find a correlation between the concentrations of PIIINP and the degree of liver damage in the available literature.…”
Section: Discussionsupporting
confidence: 58%
“…Based on the results, he concluded that patients who developed severe liver fibrosis had significantly higher concentrations of PIIINP (1208 ± 154 cpm/mg) than patients who did not develop liver fibrosis (734 ± 138 cpm/mg) (Torres-Salinas et al 1986). His findings were confirmed by other scientists in various research centers (Bentsen et al 1978, Nouchi et al 1987, Trinchet et al 1992, Oberti et al 1997, Tran et al 2000, Stickel et al 2001). However, we failed to find a correlation between the concentrations of PIIINP and the degree of liver damage in the available literature.…”
Section: Discussionsupporting
confidence: 58%
“…64,87,88 Reduction or normalization of PIIINP levels has been observed in those who abstain from alcohol. 89,90 In chronic HCV, PIIINP levels have not been shown to correlate with degree of fibrosis but do correlate with the scores for necrosis. 91,92 In patients receiving methotrexate, PIIINP appears to be a useful test for the evaluation of liver injury.…”
Section: Piiinpmentioning
confidence: 99%
“…Lobular inflammatory activity and severity of liver steatosis were determined according to the criteria of the Chinese Medical Association Committee of Fatty Liver Disease in 2006 and Nouchi et al [18,19] . [20] , which grades fibrosis on a five-point scale: Grade 0, no fibrosis; Grade 1, portal fibrosis without septa; Grade 2, portal fibrosis with a few septa; Grade 3, numerous septa without cirrhosis; and Grade 4, cirrhosis.…”
Section: Light Microscopymentioning
confidence: 99%